Evaluating Proton Dose and Associated Range Uncertainty Using Daily Cone-Beam CT - Li, Heng; Hrinivich, William T.; Chen, Hao; Sheikh, Khadija; Ho, Meng Wei; Ger, Rachel; Liu, Dezhi; Hales, Russell Kenneth; Voong, Khinh Ranh; Halthore, Aditya; Deville, Curtiland (Frontiers in Oncology, 2022)
Purpose: To quantitatively evaluate the range uncertainties that arise from daily CBCT images for proton dose calculation compared to CT using a measurement-based technique. Methods: For a head and a thorax phantom, wedge-shaped IMPT treatment plans were created such that the gradient of the wedge intersected and was measured with a 2D ion chamber array. The measured 2D dose distributions were compared with 2D dose planes extracted from the dose distributions using the IMPT plan calculated on CT and CBCT. Treatment plans of a thymoma cancer patient treated with breath hold (BH) IMPT were recalculated on 28 CBCTs and 9 CTs, and the resulting dose distributions were compared. Results: The range uncertainties for head phantom were determined to be 1.2% with CBCT, compared to 0.5% for CT, whereas the range uncertainties for thorax phantom were 2.1% with CBCT, compared to 0.8% for CT. For the thymoma patient, the primary source of anatomy change was the BH uncertainty, which could be up to 8 mm on SI direction. The dose calculated on the CBCT and CT were similar with similar anatomy changes. Conclusion: We developed a measurement-based range uncertainties evaluation method with high sensitivities and used it to validate the accuracy of CBCT based range and dose calculation. Our study demonstrated that the CBCT based dose calculation could be used for daily dose validation in selected proton patients.